Experimental Verification of Single‐Type Electron Population in Indium Tin Oxide Layers. Issue 8 (5th July 2022) - Złotnik, Sebastian; Pianelli, Alessandro; Boguski, Jacek; Kojdecki, Marek A.; Moszczyński, Paweł; Parka, Janusz; Wróbel, Jarosław
Abstract : Accurate determination of electronic transport properties of individual transparent conductive oxide layers, namely indium tin oxide (ITO), is essential for further development and design of photonic devices with ITO layer as a tunable ultrafast optoelectronic component. Precise magnetotransport measurements are here implemented to achieve carrier mobility distribution that gives insight into types and characteristics of carrier species. ITO thin films with various sheet resistance of ≈10, 75, and 350 Ω sq −1, respectively, are examined at near‐room temperature. Unimodal mobility distribution is revealed in ITO films, independently on their resistivity, with no evidence of unseparated contributions from surface or interface states. The electron mobility varies depending on ITO's resistivity, ranging from 36.8 to 47.2 cm 2  V −1  s −1 at 300 K. Importantly, no minority hole conduction is present. The ITO thin films exhibit solely bulk‐like conduction with an absence of parallel conductions. In addition, the existence of single‐type electron population in ITO that can be viewed as an important validation of exclusively donor‐type defects and/or impurities contributing to total ITO conductivity is experimentally confirmed. These results indicate that ITO can be viewed as an integrated counterpart for photonic metadevices. Abstract : Indium tin oxide (ITO) is a well‐known transparent conductive oxide implemented in several optoelectronic applications. Magnetotransport measurements with mobility spectrum analysis are applied to evaluate electronic transport properties. It is experimentally proven that ITO films exhibit solely electron conduction. The outcomes confirm that ITO can be considered as an important key component in novel photonic applications.